Uji Aktivitas Daya Hambat terhadap Bakteri Gram Positif dan Bakteri Gram Negatif Menggunakan Metode Sumur Difusi - Eli Dana Sari (JURNAL BIOSHELL, 2021)
Antibiotics are chemical compounds that can be produced by certain microorganisms and can inhibit growth or kill microorganisms. Antibiotics can also be produced by plant cells which are produced from secondary metabolites of the plant itself. To determine the potential or inhibitory activity of an antibiotic against the growth and development of bacteria, a microbiological assessment can be carried out using the diffusion disk method (filter paper (Kirby and Bauer)). As many as seven disk were made of NA (Nutrient Agar) media in a Petri dish. Each sample was sorted to obtain sufficient liquid extract. The extract pipette of each sample with the micropipette in the diffusion disk provided is labeled. The diffusion disk was then inoculated in an incubator using a temperature of 37oC for 48 hours. Negative control (sterile water), positive control (antibiotic Amoxicillin). Inhibition activity of ginger rhizome extract on Gram-positive bacteria was 36.75%, and Gram-negative bacteria was 42.29%. The inhibitory activity of betel leaf extract on Gram positive bacteria was 18.97%, and Gram negative bacteria was 16.6%. Inhibition activity of turmeric rhizome extract on Gram positive bacteria was 17.39%, Gram negative bacteria was 20.94%. The inhibitory activity of juwet leaf extract had the largest percentage of Gram-positive and Gram-negative as much as 73.12%. Meanwhile, the inhibitory activity of mint leaf extract with the smallest inhibition percentage was Gram positive and Gram negative was 0%. Keywords: antibiotics, Nutrient Agar, gram positive bacteria, gram negative bacteria, diffusion disk method